The Making of Spiritual Feminist Authority: Rethinking Women’s Religious Authority through Theological Anthropology - Sulaiman, Sulaiman; Syukur, Suparman; Muhibbin, Muhibbin (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2026)
Existing scholarship on Muslim women’s religious authority has predominantly explained legitimacy through institutional leadership, scriptural expertise, or charismatic influence, while paying limited attention to transcendental experience as a source of public religious authority. This study examines the writings of Nyai Masriyah Amva through documentary research, thematic content analysis, and Ricoeurian hermeneutics, integrating lived religion with theological anthropology to analyze how divine intimacy becomes socially recognized authority. The findings demonstrate that sustained encounters with the Divine are progressively translated into ritual discipline, symbolic mediation, ethical embodiment, and communal recognition, forming a recursive process through which religious legitimacy is constituted. Rather than functioning as private spirituality, transcendental experience becomes an epistemic resource that generates enduring moral credibility within the pesantren. The study advances the concept of spiritual feminist authority, repositioning transcendence as a constitutive dimension of women’s religious authority and offering a transferable analytical framework for understanding how lived spiritual experience is transformed into publicly recognized religious leadership across diverse religious contexts.